Multi-Functional Development and Utilization of Rapeseed: Comprehensive Analysis of the Nutritional Value of Rapeseed Sprouts - Zelin Xiao; Yuying Pan; Chao Wang; Xiongcai Li; Yiqing Lu; Ze Tian; Lieqiong Kuang; Xinfa Wang; Xiaoling Dun; Hanzhong Wang (Foods, 2022)
Rapeseed is the third largest oil crop in the world and the largest oil crop in China. The multi-functional development and utilization of rapeseed is an effective measure for the high-quality development of rapeseed industry in China. In this study, several basic nutrients of eight rapeseed sprouts and five bean sprouts (3–5 varieties each) were determined, including sugar, crude protein, crude fiber, vitamin E, minerals, fatty acids, amino acids, and glucosinolates. Data analysis revealed that compared with bean sprouts, rapeseed sprouts were nutritionally balanced and were richer in active nutrients such as glucose, magnesium, selenium, vitamin E, and glucosinolate. Moreover, rapeseed sprouts exhibited reasonable amino acid composition and abundant unsaturated fatty acids (accounting for 90.32% of the total fatty acids). All these results indicated the potential of rapeseed sprout as a functional vegetable. Subsequently, three dominant nutrients including vitamin E, glucosinolate, and selenium were investigated in seeds and sprouts of 44 B. napus L. varieties. The results showed that germination raised the ratio of α-tocopherol/γ-tocopherol from 0.53 in seeds to 9.65 in sprouts, greatly increasing the content of α-tocopherol with the strongest antioxidant activity among the eight isomers of vitamin E. Furthermore, germination promoted the conversion and accumulation of glucosinolate components, especially, glucoraphanin with strong anti-cancer activity with its proportion increased from 1.06% in seeds to 1.62% in sprouts. In addition, the contents of selenium, vitamin E, and glucosinolate in rapeseed sprouts were highly correlated with those in seeds. Furthermore, these three dominant nutrients varied greatly within B. napus varieties, indicating the great potential of rapeseed sprouts to be further bio-enhanced. Our findings provide reference for the multi-purpose development and utilization of rapeseed, lay a theoretical foundation for the development of rapeseed sprout into a functional vegetable, and provide a novel breeding direction.